Acute kinematics and kinetics changes to wearable resistance during change of direction among soccer players - Li, X.; Li, C.; Cui, Y.; Wong, D. P. (Research in Sports Medicine, 2021)
This study determined the acute changes in kinematics and kinetics when an additional load equivalent to 5% body mass was attached to the torso during change of direction (COD). In this within-subject repeated measures study, 14 male soccer players (age: 18.29±0.32years) volunteered to participate. Subjects performed COD under two conditions in randomized order: (1) no WR, and (2) with WR. No significant differences between the loaded and unloaded conditions in actual COD angle, approach speed, braking time, propulsive time, contact time, COD completion time (all p >0.05, ES=0.05-0.11), and all measured kinematic parameters (all p >0.05, ES=0-0.18). Nonetheless, ankle plantar/dorsi flexion ROM had possibly small increase in the loaded condition (ES=0.24). Kinetics analysis has shown that the loaded condition was likely to have small increase in relative peak vertical propulsive ground reaction force (GRF, p =0.11, ES=0.41), and possible small increases in relative peak braking GRF (vertical: p =0.21, ES=0.42; total: p =0.22, ES=0.38), relative peak total propulsive GRF (p=0.24, ES=0.26), and relative braking impulse (horizontal, vertical, and total; p =0.27-0.41, ES=0.26-0.28). WR did not significantly change the acute movement techniques, meanwhile induced small increases in important kinetic stimuli for potential adaptation in COD.